MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF EKSPOSISI DENGAN MODEL PEMBELAJARAN KONSTRUKTIF - Lili Feranti Manullang (Universitas Negeri Medan, 2012)
The results of studies that have been done when the author followed the practice field in 2010 showed the students' writing skills are at unfavorable category. This phenomenon is empirical evidence that shows students still believe that learning to write is difficult. This thinking is motivated by traditional learning. Alignments as a learning center teacher (Teacher Centered Learning) is often implemented in schools. Such circumstances affect the mindset of the students. So comes the difficulty of writing in their minds, and even the ability to build a low paragraphs. Therefore, constructive learning model as a foundation for contextual learning (Contextual Teaching Learning) appropriately used to improve students' writing. Constructive model is based on the constructivist philosophy that was born from the idea of ​​Piaget and Vigotsky. In simple constructive knowledge is assumed that construction (formation) of us who know something. Constructive is the process of building new knowledge in students' cognitive structure based on experience. Teacher in charge of creating a meaningful learning experience for students, which in turn will spur students to be active and creative ideas poured into the form of a paragraph contains the knowledge or exposition. In a sense, knowledge is built through experience is poured into a form meaningful paragraphs of exposition. Kata Kunci : Model Konstruktif, paragraf eksposisi, pengetahuan baru, CTL